2021
DOI: 10.3390/pathogens10070825
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Using High-Throughput Proteomics to Underpin the Discovery of Animal Host–Nematode Interactions

Abstract: Parasitic nematodes impose a significant public health burden, and cause major economic losses to agriculture worldwide. Due to the widespread of anthelmintic resistance and lack of effective vaccines for most nematode species, there is an urgent need to discover novel therapeutic and vaccine targets, informed through an understanding of host–parasite interactions. Proteomics, underpinned by genomics, enables the global characterisation proteins expressed in a particular cell type, tissue and organism, and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 92 publications
(122 reference statements)
0
5
0
Order By: Relevance
“…For example, two independent analyses of T. muris EV proteomes yielded different data [142,143] and this highlights the need for a standardized pipeline for the characterization of nematode derived EVs, as outlined elsewhere [5]. Continued proteome comparisons across relevant parasitic nematodes and life stages will aid the identification of proteins of interest that will seed functional characterization and reveal novel biomarkers and vaccine targets [120,124].…”
Section: Strongyloides Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, two independent analyses of T. muris EV proteomes yielded different data [142,143] and this highlights the need for a standardized pipeline for the characterization of nematode derived EVs, as outlined elsewhere [5]. Continued proteome comparisons across relevant parasitic nematodes and life stages will aid the identification of proteins of interest that will seed functional characterization and reveal novel biomarkers and vaccine targets [120,124].…”
Section: Strongyloides Proteomicsmentioning
confidence: 99%
“…Over the past 10-15 years significant progress has been made in proteomics platforms for identification of nematode somatic proteins that hold potential as biomarkers or therapeutic targets [124]. Life stage-specific somatic proteomics data exist for several parasitic nematode species including Trichinella spiralis, H. contortus, H. polygyrus and Nippostrongylus brasiliensis that enable species and life stage comparative analyses [125][126][127][128][129][130].…”
Section: (B) Comparison With Other Parasitic Nematodesmentioning
confidence: 99%
“…In parasitological studies, most proteomic analyses are used to understand the biological characteristics of eggs or adult parasites, explore the protein profiles at different developmental stages, and analyze the protein differences at different stages or at the same stage ( Di Maggio et al, 2022 ; Li et al., 2021 ; Wang et al., 2021 ; Wang et al., 2020 ; Hu et al., 2018 ; Wang et al., 2018 ). There are several research reports on the proteomics of H. contortus and its host animals.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, DIA deep proteomic analysis of Toxocara canis infection revealed that protein alterations were affected by disease development, confirming that the DIA is an ideal method for quantifying protein changes in microbiological infection ( Zheng et al., 2021 ). A DIA quantitative proteomic approach was also used to select biomarkers in the serum for the early clinical monitoring of B. microti infection ( Wang and Gasser, 2021 ). Therefore, proteomic research will provide new insights into the developmental biology of parasites, contribute to the discovery of novel regulated proteins, and enhance the understanding of pathogen−host interactions from the parasite perspective.…”
Section: Introductionmentioning
confidence: 99%
“…The next two review articles by Wang and Gasser and Bennett and Robinson summarise progress in the use of mass spectrometry-based proteomics techniques to study nematode and trematode parasites, respectively. With an emphasis on emerging technologies, both reviews pin-point key research areas that will enhance our understanding of host–helminth interactions with a view toward new methods of treatment and diagnosis [ 17 , 18 ]. Finally, Porras-Silesky et al review the current understanding of how the nematode parasite, Spirocerca lupi , induces cancer in dogs [ 19 ].…”
mentioning
confidence: 99%